2012
DOI: 10.1093/ehjci/jes069
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preload on left atrial function: evaluated by tissue Doppler and strain imaging

Abstract: Both tissue velocity and SR during late diastole, representing the contractile function of the LA, are relatively preload-independent parameters and are available for the evaluation of the LA function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 38 publications
4
25
0
Order By: Relevance
“…Second, studies on hemodialysis patients showed that LVEDD is significantly reduced after hemodialysis (i.e. after volume depletion) whereas A wave velocity remains unchanged[ 63 , 64 ]. Third, these studies also showed that LA volume is significantly reduced after hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Second, studies on hemodialysis patients showed that LVEDD is significantly reduced after hemodialysis (i.e. after volume depletion) whereas A wave velocity remains unchanged[ 63 , 64 ]. Third, these studies also showed that LA volume is significantly reduced after hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Data suggest that tissue Doppler may have a role in evaluating diastolic function in HD patients above traditional Doppler measurements [41], but this modality was not available at our institution at the initiation of the study. Further, signi icant evidence exists showing tissue Doppler is not independent of preload in ESRD patients [41][42][43][44]. The optimal timing of TTE for hemodynamic assessment in ESRD is yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations: It is known that LA pressure is labile; we have not tested any potential variability in strain rate measurements with fluctuations in LA pressure. An obvious disadvantage with the proposed PVR formula is that LASRa is an intrinsic active myocardial measurement, thus not suitable for patients with atrial arrhythmias, for example, fibrillation . Myocardial speckle tracking measurements remain to be vendor dependent; therefore, absolute strain rate values should be applied with caution and using the same apparatus for the clinical follow‐up of patients and their response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…An obvious disadvantage with the proposed PVR formula is that LASRa is an intrinsic active myocardial measurement, thus not suitable for patients with atrial arrhythmias, for example, fibrillation. 32,33 Myocardial speckle tracking measurements remain to be vendor dependent; therefore, absolute strain rate values should be applied with caution and using the same apparatus for the clinical follow-up of patients and their response to treatment. Technical precision of tracking LA myocardium should be emphasized because of its thin wall, particularly in patients with dilated cavity and hence even thinner walls than normal as well as those with dilated right atrium and squashed LA.…”
Section: Discussionmentioning
confidence: 99%